(untitled) (International Journal of Health, Animal Science and Food Safety, 2015)
Misuse of fluoroquinolones in livestock production may lead to the presence of their residues in tissues of meat animals after slaughter, constituting health hazards to consumers. The present study was designed to screen for residues of three fluoroquinolones (ciprofloxacin, norfloxacin and ofloxacin) in raw meat. Microbiological assay, followed by High Performance Liquid Chromatography (HPLC) was used to screen three hundred and twenty samples of beef, chicken, pork and chevon purchased from open markets. Initial screening by microbiological assay revealed that 50%, 55%, 40% and 40% of beef, chicken, pork and chevon, respectively were positive for residues of antibiotics. Further analysis by HPLC with UV detection revealed the presence of ciprofloxacin, norfloxacin and ofloxacin at varying concentrations in the meat samples. Ofloxacin was the least in frequency and abundance in all meat types. Results obtained in this study have implications for public health and will lead to steps that will further enhance the safety of animal foods in order to protect consumers and the animal production industry